Pengaruh Kualitas Layanan Akademik Terhadap Kepuasan dan Kepercayaan Mahasiswa STIE Widya Persada - Intan Arsitia; Mahar Malindo; Vinna Octaviana (Jurnal Riset dan Inovasi Manajemen, 2026)
Higher education institutions are not only expected to produce a large number of graduates but also to develop qualified and highly disciplined human resources who are capable of becoming dynamic agents, innovators, motivators, and drivers of development across various fields and levels of expertise. Therefore, higher education institutions must pay close attention to the quality of services provided to students. STIE Widya Persada is a higher education institution committed to improving the quality of services provided to its students. Improving service quality is expected to enhance student satisfaction and trust, which may ultimately contribute to student loyalty. This study aims to identify the effect of academic service quality on student satisfaction and trust and to examine their impact on student loyalty. The research employed the Partial Least Squares (PLS) method using SmartPLS version 4.1.1.8 software. The results indicate that service quality plays an important role in maintaining student loyalty. Excellent academic services can increase student satisfaction and trust, thereby fostering stronger student loyalty toward the university